Selection оf Parameters for System of Diesel Engine Exhaust Gas Recirculation - G. M. Kukharionok; V. I. Berezun (Наука и техника)
The paper presents research results of various methods for recirculation of diesel engine exhaust gases. An influence of recirculation parameters on economic and ecological diesel engine characteristics has been evaluated in the paper. The paper considers an influence of turbocharger configuration on the intensity of gas recirculation. Specific features of the recirculation system operation in dynamic modes have been shown in the paper. The paper provides recommendations for selection of a diesel engine exhaust gas recirculation system.